Impact of diabetes on coronary severity and cardiovascular outcomes in patients with heterozygous familial hypercholesterolemia: an analysis of genotype and phenotype. (14th October 2021) - Liu, M M; Li, J J
Abstract: Aims: Type 2 diabetes mellitus (T2DM) is an independent risk factor for cardiovascular disease. However, the association between T2DM and coronary artery disease (CAD) in patients with heterozygous familial hypercholesterolemia (HeFH) has not been thoroughly evaluated. Our study aimed to assess the effect of T2DM on CAD severity and hard cardiovascular endpoints in a HeFH cohort. Methods: A total of 432 patients with HeFH with a molecular and/or clinical Dutch Lipid Clinic Network score ≥6 (definite and probable) were enrolled. Patients were divided into a T2DM group (n=99) and a non-T2DM group (n=333). Hard endpoints included a composite of non-fatal myocardial infarction, stroke, and cardiac death. Results: No differences were observed regarding genetic mutations in patients with and without T2DM. Patients with T2DM demonstrated a greater number of diseased vessels (p=0.029) and more severe coronary lesions with high Gensini, SYNTAX, and Jeopardy score tertiles. Compared with patients without T2DM, patients with T2DM were at a significantly greater risk of hard endpoints (multivariate adjusted hazard ratio [HR] 2.32, 95% confidence interval [CI] 1.02–4.84, p=0.025). Additionally, patients with T2DM and good glucose control (HbA1c <7.0%) were at a lower risk of hard endpoints compared with those with poor glucose control (HbA1c ≥7.0%, HR 0.08, 95% CI 0.01–0.56, p=0.011). Conclusions: We conclude that T2DM is an independent predictor of CAD severity when assessed by four different tests and worse cardiovascular outcomes, suggesting that T2DM could be further used for risk stratification of patients with HeFH. Funding Acknowledgement: Type of funding sources: None.